2018
DOI: 10.1111/jcmm.14030
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of miR‐29b and miR‐200b in type 2 diabetic retinopathy

Abstract: MicroRNAs (miRNAs/miRs) are involved in the pathogenesis of diabetes mellitus and its chronic complications, and their circulating levels have emerged as potential biomarkers for the development and progression of diabetes. However, few studies have examined the expression of miRNAs in diabetic retinopathy (DR) in humans. This case‐control study aimed to investigate whether the plasma levels of miR‐29b and miR‐200b are associated with DR in 186 South Brazilians with type 2 diabetes (91 without DR, 46 with non‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…For instance, endothelial miR-200b overexpression prevents diastolic dysfunction and endothelial-to-mesenchymal transition, preserving, therefore, cellular integrity and preventing diabetes-induced adverse myocardial structural and functional changes [131] (Table 1). Importantly, very recently, a report was published showing that levels of miR-200b are lower in patients with T2DM than in control ones [132] (Table 1). Further studies are required in order to elaborate on the different protective and/or adverse impacts that each member of the miR-200 family has in a cell and disease dependent manner in order to optimize any potential therapeutic approach.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…For instance, endothelial miR-200b overexpression prevents diastolic dysfunction and endothelial-to-mesenchymal transition, preserving, therefore, cellular integrity and preventing diabetes-induced adverse myocardial structural and functional changes [131] (Table 1). Importantly, very recently, a report was published showing that levels of miR-200b are lower in patients with T2DM than in control ones [132] (Table 1). Further studies are required in order to elaborate on the different protective and/or adverse impacts that each member of the miR-200 family has in a cell and disease dependent manner in order to optimize any potential therapeutic approach.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…In recent years, several works have investigated the association of miRNAs with DR (23)(24)(25)(26)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In circulating miRNA profiling studies, miR-27b, miR-320a, and miR-126 were validated in patients with type 1 diabetes and DR (23,42).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-222 protects against cardiac injury and miR-17-3p promotes cardiomyocyte proliferation and increased cardiomyocyte size through directly targeting TIMP3 (Wang et al, 2018). miR-29b is one of the first miRNAs that was found to be dysregulated in retinal cells and diabetic rats exposed to high glucose concentrations, suggesting that they are involved in the development of DM (Dantas da Costa E Silva et al, 2019). A recent in vivo study showed that miR-29b is involved in regulation of glucose balance and insulin secretion through a variety of target genes and influences the pathogenesis of diabetes (Dooley et al, 2016).…”
Section: Discussionmentioning
confidence: 99%